Intensification of Cropping through Utilization of Fallow Period and Unutilized Land Resources in Bangladesh (Bangladesh Rice Journal, 2021)
Unavailability of suitable technologies including stress-tolerant cultivars, management options, irrigation facilities as well as extension supports are the key challenges for intensification of cropping through horizontal and vertical extension approaches. This study assesses the potential for increasing rice production through a horizontal extension approach. Historical and projected trend of area and production of rice, major cropping patterns and cropping intensity, as well as expert opinion, were the basis for extrapolation of the intensity of cropping by 2030. The analysis shows that about 1.52 M ha area with fallow period of the existing major cropping patterns and 0.65 M ha fallow land is potential for additional rice cropping. Resulting from that about 5.8 million tons additional rice can be added to total rice production in the country. An inclusion of a rice crop in certain percentage of the existing major cropping patterns, such as Boro-Fallow-T. Aman (25%), Boro-Fallow-Fallow (50%) and Fallow-Fallow-T. Aman (40%) may contribute, respectively 1.38 million tons, 1.57million tons and 0.80 million tons of rice in the total rice production. Besides, the addition of a certain percentage of cultural waste (50%), marshy land (25%), newly developed char land (50%), and Jhum (60%) and other extrapolation areas of Chittagong Hill Tract, respectively may contribute 0.4 million tons, 0.25 million tons, 0.34 million tons and 0.06 million tons rice in the total rice production. Strategic policy supports are required for implementing appropriate action plans to achieve the goals.Bangladesh Rice J. 25 (1) : 89-100, 2021